2008
DOI: 10.1021/ja8052706
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Oxidation Stability of Glycals: Excellent Substrates for Cerium(IV)-Mediated Radical Reactions

Abstract: Abstract:The remarkable stability of glycals under oxidative conditions becomes apparent by their redox data in solution, computed HOMO energies, and behavior on the addition of electrophilic radicals generated in the presence of cerium(IV) ammonium nitrate. Oxidation potentials up to 2.03 V vs ferrocene were obtained, which are exceptionally high for cyclic enol ethers but correlate nicely with the reaction times of the radical reactions. Protecting groups have a strong influence on the oxidation stability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 91 publications
(49 reference statements)
3
27
0
Order By: Relevance
“…Modification of Schreiners reaction for use in stereoselective glycosylations was not a trivial task, as the physical properties and solubilities of our substrates were not amenable to the methods described. [13] We optimized the reaction of protected galactal 2 a [15] (1.2 equiv.) with model acceptor 3 a and found that 1 mol % of catalyst 1, in a solution of CH 2 Cl 2 heated to reflux, gave excellent results.…”
mentioning
confidence: 99%
“…Modification of Schreiners reaction for use in stereoselective glycosylations was not a trivial task, as the physical properties and solubilities of our substrates were not amenable to the methods described. [13] We optimized the reaction of protected galactal 2 a [15] (1.2 equiv.) with model acceptor 3 a and found that 1 mol % of catalyst 1, in a solution of CH 2 Cl 2 heated to reflux, gave excellent results.…”
mentioning
confidence: 99%
“…48-50 The remarkable stability of glycals under oxidative conditions was justified by their redox data in solution. 51 The [3þ2] cycloaddition of 2-hydroxy-1,4-naphthoquinone 17 to alkenes mediated by CAN resulted in the formation of furo-p-quinones as well as o-quinone derivatives. 52 This was further utilized for the synthesis of phenalenofuranones, 53 furopyranones, furoquinolinones, 54 and dihydrofuropyrimidinediones.…”
Section: Intermolecular Carbon-carbon Bond Forming Reactionsmentioning
confidence: 99%
“…All additions are orbital-controlled and give exclusively one regioisomer, in agreement with the HOMO energies and coefficients of all glycals 6, which we previously determined by cyclic voltammetry and calculation. [17] The excellent stereoselectivities of the reactions are due to steric interactions with the O-acetyl groups, in accordance to radical additions to glycals.…”
mentioning
confidence: 94%